Ethanol Dry Reforming for Syngas Production Over Ce-promoted Ni/Al2O3 Catalyst - Mahadi, Bahari; Phuc, Nguyen Huu Huy; Bawadi, Abdullah; Alenazey, Feraih; Vo, Dai-Viet N. (Elsevier Ltd, 2016)
Ce-promoted and unpromoted 10%Ni/Al2O3 catalysts were prepared by co-impregnation method and evaluated for ethanol dry reforming in a quartz fixed-bed reactor at different CO2:C2H5OH ratios of 2.5:1 to 1:2.5 and temperature of 923–973 K under atmospheric pressure. Thermogravimetric studies indicated that both catalysts were completely calcined and subsequently reduced to metallic Ni° phase. The addition of Ce promoter facilitated the reduction process and decreased reduction temperature by about 315 K. Stronger metal-support interaction was observed with Ce addition. NiO and NiAl2O4 phases were formed on catalyst surface during calcination for both catalysts whilst CeO2 form was identified on promoted catalyst. Significant enhancement of ethanol conversion up to 75.2% with reaction temperature was observed and catalytic activity appeared to be stable with time-on-stream at beyond 5–7 h for both promoted and unpromoted catalysts. C2H5OH and CO2 conversions increased with growing CO2 partial pressure whilst the optimal C2H5OH partial pressure was obtained at about 30–40 kPa for both catalysts. C2H5OH conversion was always greater than that of CO2 indicating the co-existence of side reactions, namely; ethanol decomposition and dehydrogenation during ethanol dry reforming reaction. Ce-addition improved both C2H5OH and CO2 conversions irrespective of reactant partial pressure. Although both carbon nanofilament and graphitic carbon were detected on the surface of spent catalysts by SEM, TEM and Raman measurements, the proportion of carbon nanofilament was dominant and the percentage of amorphous carbon was increased with Ce promoter.